2013
DOI: 10.1002/asna.201211975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the possible Blazhko‐effect Cepheid V473 Lyrae

Abstract: The dates of receipt and acceptance should be inserted later Key words Cepheids -stars: individual (V473 Lyr) V473 Lyrae is a peculiar Galactic Cepheid, showing strong amplitude modulation that resembles the Blazhko-effect observed in RR Lyrae stars. We collected data spanning several modulation cycles and started a detailed analysis. The first results indicate that the star shows both amplitude and phase modulations with an average period of 1204 days, but both the cycle length and the strength of the modulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…It is much less common among other radial pulsators, however. Despite the fact that we know many double-mode Cepheids with amplitude and phase modulations [1], there is only one Galactic Cepheid (V473 Lyrae) with confirmed periodic amplitude and phase variations similar to the Blazhko effect observed in RR Lyrae stars [2].…”
Section: Introductionmentioning
confidence: 89%
“…It is much less common among other radial pulsators, however. Despite the fact that we know many double-mode Cepheids with amplitude and phase modulations [1], there is only one Galactic Cepheid (V473 Lyrae) with confirmed periodic amplitude and phase variations similar to the Blazhko effect observed in RR Lyrae stars [2].…”
Section: Introductionmentioning
confidence: 89%
“…However, several studies have shown that, in addition to the secular period changes known since long (Szabados 1983;Berdnikov & Ignatova 2000;Pietrukowicz 2001Pietrukowicz , 2002Poleski 2008;Turner et al 2006), fluctuations of pulsation periods and amplitudes are present in some, if not all, Cepheids. An early example of this was V473 Lyr, which exhibits periodic variations of its light and radial velocity amplitude, similar to RR Lyrae stars exhibiting the Blazhko effect (Burki et al 1982;Molnár et al 2013). Space-based photometry obtained with the Kepler, MOST, and BRITE satellites has revealed a host of variations in the fundamentalmode Cepheid V1154 Cyg (Derekas et al 2012;Kanev et al 2015;Derekas et al 2017), found long-period modulation in T Vul (Smolec et al 2016a) and suggested a greater degree of irregularity exhibited by first-overtone (FO) Cepheids (Evans et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Anderson (2014, henceforth: A14) reported the discovery of modulated radial velocity (RV) variability of four Cepheids, two of which-QZ Nor and V335 Pup-are short-period Cepheids likely to pulsate in the first overtone and candidates for Blazhko-effect-like long-timescale modulations (years) similar to the enigmatic V473 Lyr (Burki et al 1982;Molnár et al 2013). The two additional Cepheids presented in A14-Car and RS Pup-are long-period Cepheids for which significant RV curve modulations among consecutive pulsation cycles were detected, varying in particular the RV amplitude.…”
mentioning
confidence: 99%